A PERFORMANCE-BASED BUILDING CODE IN USE - KEVIN NEWHOUSE, KEVIN NEWHOUSE (Penerbit UTM Press, 2001)
The trend in development of building codes has been to move away from prescriptive codes that describe a particular method that must be complied with, to performance-based or objective-based codes that describe the outcome or level of performance to be achieved. The development of the Building Code of Australia followed this trend, with a fully performance-based version of the code being released in 1996.